Electrospun fibers: an innovative delivery method for the treatment of bone diseases. (2nd July 2020) - Mao, Yingji; Zhao, Yupeng; Guan, Jingjing; Guan, Jianzhong; Ye, Tingjun; Chen, Yu; Zhu, Yansong; Zhou, Pinghui; Cui, Wenguo
ABSTRACT: Introduction: The treatment performances of current surgical therapeutic materials for injuries caused by high-energy trauma, such as prolonged bone defects, nerve-fiber disruptions, and repeated spasms or adhesions of vascular tendons after repair, are poor. Drug-loaded electrospun fibers have become a novel polymeric material for treating orthopedic diseases owing to their three-dimensional structures, thus providing excellent controlled drug-release responses and high affinity with local tissues. Herein, we reviewed the morphology of electrospun nanofibers, methods for loading drugs on the fibers, and modification methods to improve drug permeability and bioavailability. We highlight innovative applications of drug-loaded electrospun fibers in different treatments, including bone and cartilage defects, tendon and soft-tissue adhesion, vascular remodeling, skin grafting, and nervous-system injuries. Areas covered: With the rapid development of electrospinning technologies and advancement of tissue engineering, drug-loaded electrospun fibers are becoming increasingly important in controlled drug release, wound closure, and tissue regeneration and repair. Expert opinion: Drug-loaded electrospun fibers exhibit a broad range of application prospects and great potential in treating orthopedic diseases. Accordingly, a plethora of novel treatments utilizing the different morphological features of electrospun fibers, the distinctive pharmacokinetics, pharmacodynamics characteristics of different drugs, and the diverse onset characteristics of different diseases, is proposed.